Exploration of Iron Sand at The Eastern Coast Area of Binangun in Cilacap Regency Using Magnetic Survey - Sehah Allasimy; Sukmaji Anom Raharjo; Iska Andriyanto (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2017)
Exploration of the spread of iron sand on the eastern coastal of Binangun District in Cilacap Regency has been conducted using the magnetic surveys. The magnetic data acquisition was conducted in April 2017. The total magnetic field data obtained is processed, so that can be obtained the local magnetic anomaly data. The modeling of the local magnetic anomaly data is performed on the trajectory of AB that extending from the position point of 109,274698° E and 7.686620° S to 109.2296195° E and 7.689099° S so that obtained various model of the subsurface anomalous objects. Interpretation on the subsurface anomalous objects is done to estimate the types of rocks and their formations based on the magnetic susceptibility value of each object which supported by the geological information of the research area. Based on the interpretation results to be obtained two layers of subsurface rocks that can be estimated as the iron sand that coexists with silt dan clay derived from the alluvium formation. The first rock has a length of 1238.2 meters, a depth of 1.709 – 20.513 meters, and a magnetic susceptibility value of 0.0183 cgs unit. The second rock has a length of 643.055 meters, a depth of 16.524 – 34.188 meters, and a magnetic susceptibility value of 0.0174 cgs unit. The results of this research are also supported by the results of geoelectric data interpretation, where the iron sand that coexists with silt and clay is found at a depth of 9.42 – 19.48 meters with a resistivity value of 52.99 Ωm at Geo-1 point; and a depth of 10.56 – 22.20 meters with resistivity value of 49,03 Ωm at Geo-2 point. Based on the results of of this research, the eastern coastal area of Binangun District is estimated to contain potentially iron ore and economically is a prospect for exploitation.